Nanocomposite Coatings: Stable Interface between Lithium and Electrolyte Facilitated by a Nanocomposite Protective Layer (Small Methods 3/2020). Issue 3 (6th March 2020) - Yang, Luyi; Song, Yongli; Liu, Hao; Wang, Zijian; Yang, Kai; Zhao, Qinghe; Cui, Yanhui; Wen, Jiayun; Luo, Wei; Pan, Feng
Abstract : In article number 1900751 by Wei Luo, Feng Pan, and co‐workers, a facile and rapid coating strategy is proposed to form a nanocomposite protecting layer on Li metal anodes. This layer serves as an artificial solid‐electrolyte interface film that remains stable after repeated cycling. The coated Li exhibits greatly improved stability with Li1.3 Al0.3 Ti1.7 PO4 solid electrolyte by inhibiting the interfacial reaction interface, and therefore, excellent cycling stability is obtained.